Hubungan Beban Tas Dengan Terjadinya Skoliosis Postural Pada Anak Sekolah Dasar Usia 10-12 Tahun Di Kecamatan Gunung Jati - SEPTIANI, Pipit, Dwi Kurniawati, SSt.FT (2017)
Background: The children in elementary like some backpack models depend on their pretension. Backpack is very useful to the children for bringing their equipment but they must use well and balance, not just in one site. Using bag in one site tringgered bad posture. The big and weight of the bag, not only tringgered back pain but also in other part of the body. Scoliosis is the angle that with patologic condition. Rosadi (2009) said, 4,1 % from 2000 elementary to junior 2 high school students in Surabaya get scoliosis. Early diagnostic can give the information to the student and the family to prevent scoliosis and deformity. Purpose : For knowing the relation between weight of the bag and occuring postural scoliosis. Method : This research is observational research with cross sectional method. Taking sample technique use positive sampling. The total of samples is 57 people. Primary data is gotten from direct observation. Statistic test use pearson chi square test. Results : Respondents with weight of the bag >10% from the weight are 99 people (43.6%), weight of the bag <10% from the weight are 128 people (56.4%). While the respondents with postural scoliosis are 73 people (32.2%), not postural scoliosis are 154 people (67.8%). This data is test by pearson chi square test and get the value p = 0,001, it mean that there is the relation between the weight of the bag with occuring postural scoliosis. Conclusion : There is the relation between the weight of the bag with occuring postural scoliosis.